Propuesta de un plan de supervisión con participación democrática para mejorar la calidad de la gestión del centro educativo gustavo ries de la ciudad de Trujillo - Rojas Ruiz, Irene Jacqueline (2005)
One of the problems that stands out in the educational sector, is the evil understanding of the supervision for two reasons, first for ignorance of the involved subjects, the plans are done without his knowledge and second for lack of training of the .memos supervisors therefore the supervision is pushed back. The present work proposes a Plan of Supervision with democratic participation to improve the quality of management of the Educational Institution Gustavo Ríes in the frame of the strategic planning, in such a way that it) allows to actuate his executives inside the politics of institution building and this way same to expire with the mission and vision of the educational center. It is because of it that the present work realized with the information obtained from the diagnosis of the institution, besides the theory on educational supervision, strategic planning and methodology of planning participative, which allowed to elaborate the offer of the plan of educational supervision with democratic participation the one that consists of the following essential components: Identity of the educational institution, strategic diagnosis, direction strategic, strategic projection and evaluation of the offer. Identity that consists of the mission and vision makes an analysis a conscious internalization of the same one that is the component orientate of all the components. The work ended up by describing every component of the plan proposed in order to orientate the institutional management to offer innovation in the education and learning’s answering to the relevancy of the demands(lawsuits) of the own(proper) educational institution, offer that will be an alternative to solve the problematic before exposed.